Tendências teórico-metodológicas da formação profissional em serviço social no ensino à distância na Paraíba - Cunha, Angely Dias da (2018)
This dissertation is the result of bibliographical and documentary research based on dialectical historical materialism and its general objective is to analyze the theoretical and methodological trends present in the professional training in Social Service in Distance Education in Paraíba, based on the pedagogical projects and the formative contents expressed in the programs of the disciplines of Higher Education Institutions in the light of the ABEPSS / 1996 Curricular Guidelines. In order to learn the object through the central heuristic categories, it was searched throughout the dissertation to relate the conjuncture of capital crisis, the counterreformation of the State and its unfolding for professional training in distance education. In this ontological elucidation, it is understood the expansion of this modality of teaching as a strategy oriented by the multilateral organisms for the strengthening of the profitability of the educational market oligopolies and for reproduction of the bourgeois ideology in the construction of a neoliberal educational culture centered in the concepts of "employability" "Sustainability", "social commitment", "entrepreneurship", "collaboration" and "volunteering". These elements were identified based on the ABEPSS / 1996 Curriculum Guidelines in the analysis of the pedagogical projects and the programs of the disciplines available on the sites of the distance institutions, collected in 2017 and organized by tables containing the objectives, the conception, the profile that is intended to form, the presuppositions and principles of the professional formation present in the pedagogical projects and by disciplinary tables covering the programmatic contents and the basic bibliographies of the four studied institutions. In view of this, an educational culture of the market is affirmed, permeating vocational training at a distance and contributing to a flexible and versatile professional profile that is far from the foundations of the ethical-political project of the profession and its critical direction. It is identified a lightening, technical and pragmatic formation based on theoreticalmethodological tendencies characteristic of positivism, phenomenology, structuralism, existentialism and postmodern thought, sometimes re-updating conservatism, sometimes articulating neoconservatism in the profession. Therefore, a professional formation with gaps related to the appropriation of the ontological foundations of Social Being and work, which recovers social theories, doctrinal arrangements and conservative and neoconservative social thoughts proper to the bourgeois order through the fragmentation of teaching and combat the critical perspective by the promise through the use of Information and Communication Technologies. Distance learning institutions offer mass education through large-scale certification and disciplines that address behavior, social adjustment, and blaming individuals for their success or failure. Thus, the presence of two types of professional profiles in contention in the profession is reaffirmed: that of the critical perspective formed in IES, whose direction of training is based on the guidelines of the ABEPSS / 1996 Guidelines; and that profile formed in the conservative and neoconservative perspective in HEI whose commitment is to increase the profitability of oligopolies, to introduce values based on neoliberalism and to combat the advance of critical thinking. The incompatibility between the distance education modality and the professional political ethical project is emphasized, based on the totality of the social being whose horizon is a society beyond capital.